DEVELOPING E-LEARNING BASED LOCAL-FOLKLORES FOR EIGHTH GRADERS - Sopian Sopian; Rita Inderawati; Ismail Petrus (University of Kuningan, 2019)
The aim of this study was to develop e-learning based local-folklores application. This study was conducted based on ADDIE (Analysis, Design, Development, Implementation and Evaluation) development research design. The formative evaluation was done through one to one evaluation, small group evaluation and field trial. The subjects of this study was eighth graders at one of junior high school in Indonesia. There were three students involved in one to one evaluation, nine students in small group evaluation and a real class in a field trial. The validity was reviewed by expert of content, expert of instructional design and expert of developing e-learning based local-folklores. The mean validity score of the developed product was 3,67 which was categorized as very highly valid level. The practicality was conducted in one to one evaluation and small group evaluation. The practicality of one to one was 3,40 which was at very highly practical level and the practicality in small group evaluation was 3,58 which was at very highly practical level. The reading test material was categorized as effective. It showed that there were 19 students (76,93%) out of 26 students in reading test exceeded MMC (minimum mastery criterion) which was 75.